Demokratisering van die onderwys - Schalkwyk, O. J. van (Koers, 1985)
The democratisation of education comprises respect for the sovereignty of every consumer of education and for all who have an interest in education; it also takes the following into consideration : all relevant points of view, the life phases of the child and the reseration or unlocking of the subject matter (learning content) in past , present and future perspectives. It also implies the transmission of all learning content in full context as well as the understanding and interpretation thereof as part of and interrelated with reality as a whole (totality). The implementation of the principle of democratisation is, therefore perceived in a broader sense than is usually the case, for not only should all people be allowed their rights and opportunities, but all points of view, periods in time and contextual matters which may influence the understanding of learning content, should also be taken into account.